Halophilic Algal Communities in Biological Soil Crusts Isolated From Potash Tailings Pile Areas - Sommer, Veronika; Karsten, Ulf; Glaser, Karin (Frontiers in Ecology and Evolution, 2020)
Mining potash for fertilizer produces vast amounts of highly saline waste that is deposited in potash tailings piles. Rainfall washes the salts out, affecting the surrounding ecosystems. Only salt-tolerant organisms occur close to the piles, since other species cannot survive in these hypersaline conditions. Halophytic plant communities around tailings piles have been well investigated. However, studies exploring the biodiversity of the space behind the vegetation line that separates suitable salinities for plant growth from hostile conditions are rare. On top of the tailings piles, only micro-organisms thrive. This study, for the first time, explored the microalgae and cyanobacteria in biocrusts that in-habit potash tailings pile areas between the vegetation line and the pile body. Two biocrust types were studied: young biocrusts at or close to the tailings piles, and established biocrusts situated in the near surroundings. The estimated abundance of green algae, cyanobacteria and diatoms was studied using a direct microscopy approach, followed by the isolation and establishment of unialgal strains and morphological species determinations. Soil environmental characteristics were analyzed. Soil samples showed ECSat (electrical conductivity) values that drastically exceeded the scales commonly used to describe soil salinity, indicating extremely saline conditions. Indeed, the isolate composition was shaped by soil salinity parameters. Soil ECSat of young biocrusts tended to be higher than in estab-lished biocrusts, and filamentous green algae were most abundant. In contrast, established biocrusts tended to have a lower ECSat and were mostly dominated by filamentous cyanobacteria. Algal and cyanobacteria isolate composition differed significantly in young and established biocrusts, although the species number did not. Some of the salt-tolerant algal strains are assumed to be candidates for the formation of artificial biocrusts on the surface of the tailings. Attempts to “green” the piles by the establishment of higher plants to trap rainwater and therefore reduce the salt-output are difficult to apply. Plants require a thick layer of substrate to reduce the salinity, and the substrate easily erodes on the steep slopes. However, microalgae isolated from potash tailings pile areas seem promising, since they can survive on a thinner substrate layer and are already adapted to these hypersaline conditions.